Impacts of heart disease, depression and their combination on all-cause mortality in older people: a rural community-based cohort study in China. Issue 12 (1st December 2020) - Zhou, Weiju; Hopkins, Alex; Zaman, M Justin; Tao, Xuguang (Grant); Rodney, Amanda; Yao, Yuyou; Cao, Zhongqiang; Ma, Ying; Hu, Zhi; Copeland, John J; Chen, Ruoling
Abstract : Objective: To assess the impact of heart disease (HD) combined with depression on all-cause mortality in older people living in the community. Design: A population-based cohort study. Participants: We examined the data of 1429 participants aged ≥60 years recruited in rural areas in Anhui province, China. Using a standard method of interview, we documented all types of HD diagnosed by doctors and used the validated Geriatric Mental Status-Automated Geriatric Examination for Computer Assisted Taxonomy algorithm to diagnose any depression for each participant at baseline in 2003. The participants were followed up for 8 years to identify vital status. Measurements: We sought to examine all-cause mortality rates among participants with HD only, depression only and then their combination compared with those without these diseases using multivariate adjusted Cox regression models. Results: 385 deaths occurred in the cohort follow-up. Participants with baseline HD (n=91) had a significantly higher mortality (64.9 per 1000 person-years) than those without HD (42.9). In comparison to those without HD and depression, multivariate adjusted HRs for mortality in the groups of participants who had HD only, depression only and both HD and depression were 1.46 (95% CI 0.98 to 2.17), 1.79 (95% CI 1.28 to 2.48) and 2.59 (95% CI 1.12 to 5.98), respectively. Conclusion: Older people with both HD and depression in China had significantly increased all-cause mortality compared with those with HD or depression only, and without either condition. Psychological interventions should be taken into consideration for older people and those with HD living in the community to improve surviving outcome.